PENDEKATAN INTERDISIPLINER (SOSIOLOGIS, ANTROPOLOGIS DAN SEJARAH) - Zaimah; Sri Rahayu Lestari Putri; Misbah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic education in Indonesia, particularly that which is rooted in Malay culture, cannot be separated from social dynamics, cultural values, and the historical development of Islamic intellectual heritage (turath). However, studies on Islamic education are often conducted through a monodisciplinary lens, resulting in partial and fragmented understandings. This study aims to analyze Islamic education based on Malay culture using an interdisciplinary approach that integrates sociological, anthropological, and historical perspectives. This research employs a qualitative method with a descriptive analytical approach. Data were collected through literature review of classical Islamic texts (turath), educational documents, and relevant previous studies, and analyzed by linking social structures, cultural practices, and historical processes. The findings indicate that Islamic education rooted in Malay culture is shaped by the interaction between Islamic teachings, local wisdom, and historical contexts. The interdisciplinary approach provides a more holistic understanding of religious moderation, Islamic identity, and the continuity of Islamic educational traditions. This study concludes that integrating sociological, anthropological, and historical approaches is essential for strengthening contextual, moderate, and tradition-based Islamic education.